STRATEGIC MANAGEMENT TOWARD AN EXCELLENT SCHOOL - Akhmad Fadhilah; Ahmad Suriansyah; Sulistiyana Sulistiyana (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to describe the application of strategic management in establishing exemplary schools at SD Muhammadiyah 9 Banjarmasin and MIS Diniyah Muhammadiyah 1 Banjarmasin. This study employs a qualitative approach using a multi-case study method and descriptive techniques. Data collection was conducted through observation, in-depth interviews, and documentation. The study focused on three main strategies: human resources, partnerships, and school marketing and branding. The results indicate that the human resources strategy is implemented through recruitment based on Islamic values and competencies, regular training, performance evaluations, and personal development. The partnership strategy is carried out collaboratively with parents, social institutions, and school-based business units to strengthen internal and external support. Meanwhile, the marketing and branding strategy is implemented through digital media, educational visual content, and image enhancement based on flagship programs and parent testimonials. These three strategies are applied adaptively and contextually to improve the quality of education. This study recommends strengthening the evaluation system, innovating digital promotion, and managing sustainable partnerships to enhance the competitiveness of Modern Islamic schools.